Mathematica® na usługach ekonomii - Zawadzki, Henryk (Mathematica® at economics service, 2010)
Delay differential equations (DDEs) appeared in economic scientific papers in yearly thirties of the 20th century among others in works of R. Frisch, M. Kalecki and (slightly later) in works of J. Tinbergen and R.M. Goodwin. Some models considered in these works and some new models of this kind are sometimes presented on the lectures on mathematical economics. The purpose of this article is to present (on example of M. Kalecki‘ s business cycle model) some capabilities of computer algebra system Mathematica in solving of DDEs and graphic presentation of solutions
Didactics of Mathematics, 2010, Nr 7 (11), s. 135-142
Keywords: computer algebra systems; delay differentia equations; Kalecki‘s business cycle model; Mathematica®